Il dopo delle famiglie: disagi, quasi certezze e speranze - Corsi, Michele (Rivista Italiana di Educazione Familiare, 2021)
The paper focuses on the situation of families after coronavirus pandemic, and it is divided in three sections. An “after”, which is also a “now”, because we do not even know how long it will last. We, therefore, need to discuss the discomforts, the almost certainties and the hopes, starting from a consideration: it seems that the situations families are living these days are virtually unknown to those governing us. In addition, what it possibly even worse, the latter behave using a romanticism, which seems inappropriate and out of place. The discomforts: an excess of competences no one really possess to fight an almost unknown virus; the decisions taken by the Government and the major situations of poverty – and not only the economic one – of our Country; the distance between Power and People; and distance learning, in light of the real possibilities of Italian families. The almost certainties: an increase in separations and divorces in the near future and a worsening of already compromised family dynamics. The hops: that the State, the Church, and Pedagogy as well, work more and more fruitfully in the near future towards project and stability cultures for the families and the people, from young ones to adults.